855 Pedestrians at highest risk in Pakistan. (1st September 2016) - Tahir, Muhammed Navid; Akbar, Ali Hammad; Kayani, Ahsan; Ramadhani, Saif Al; Haworth, Narelle; King, Mark; Naseer, Rizwan
Abstract : Background: Road crashes and injuries constitute a significant public health issue in Pakistan. Growing urbanisation and motorization trends, traffic violations, encroachments and lack of road safety awareness have placed pedestrians at highest risk in Pakistan. A recent study found that pedestrians constituted 53% of the reported fatalities in Islamabad, Pakistan during 2008 to 2010. Similarly, Road Traffic Injury Research and Prevention Centre recorded 1, 130 road fatalities in Karachi during 2013, wherein 379 (33.5%) were pedestrians. The current research would be the first large scale study in the country that presents existing pedestrians safety scenario in Pakistan. Methods: Retrospective analysis of Rescue 1122 (an emergency service in Pakistan) crash data for last two years period (July 2013- June 2015) was conducted. Data were collected from 37 major cities of Province Punjab. Results: Rescue 1122 attended 407, 628 road crashes across Punjab during the study period, wherein 76, 737 pedestrians were injured. Of the total 5, 317 fatalities, about 30% ( n = 1, 577) were pedestrians, and 80% of them were males. Maximum pedestrian injuries 19, 916 (26%) were reported in Lahore, followed by 12, 285 (16%) in Faisalabad and 4, 876 (6%) in Gujranwala. Motorcycles (59%), trucks (10%) and cars (9%) were the major colliding vehicles with pedestrians. Whilst, speeding (42%), careless driving (32%) and wrong turn (12%) were the major crash contributing factors. Conclusions: Pedestrians are at highest risk in Pakistan. Speeding, careless driving, disregard of right of way, encroachments and lack of road safety awareness amongst all road users are the major factors behind increasing road crashes and pedestrians' vulnerability in Pakistan. Road crashes are not being dealt as a significant issue in Pakistan. Sustainable efforts on the part of government, transport organisations, law enforcers, community and media are required. School road safety education is also vital in this view.